Robert Copland : Poems - Copland, Robert, active 1508-1547 (Book collections on Project MUSE., 1993)
A lively pre-Renaissance world lives through the intricate and humane poetry of Robert Copland. His poetry includes a bequest of farts, a surprisingly psychologically complex satire on a bereaved widow, and the first poem of English life outside the law.